Developing Students’ Spatial Thinking and Color Perception Through Teaching Landscape Drawing - Tursunova Dilshoda Jahongirovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article explores methods for developing students’ spatial thinking and color perception through teaching landscape drawing. It examines pedagogical approaches, didactic strategies, and practical exercises that enhance students’ ability to understand spatial relationships, depth, and perspective while working with natural landscapes. The study highlights how landscape drawing fosters visual literacy, aesthetic awareness, and creative expression, and provides guidance on effectively structuring lessons to maximize students’ artistic development.